Characterization of the complete chloroplast genome of Ajuga forrestii (Lamiaceae), a medicinal plant in southwest of China - Tao, Ai-En (Mitochondrial DNA B Resour, 2019)
Ajuga forrestii is a medicinal plant commonly used in southwest of China. In this study, we sequenced the complete chloroplast (cp) genome sequence of A. forrestii to investigate its phylogenetic relationship in the family Lamiaceae. The chloroplast genome of A. forrestii was 150,492 bp in length with 38.3% overall GC content, including a large single copy (LSC) region of 82,148 bp, a small single copy (SSC) region of 17,160 bp and a pair of inverted repeats (IRs) of 25,592 bp. The cp genome contained 112 genes, including 79 protein coding genes, 29 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated Ajuga was closely related to Scutellaria.